EXPLORING THE IMPACT OF PRECONCEIVED NOTIONS ON SOCIAL RELATIONSHIP AMONG PHYSICALLY CHALLENGED LEARNERS OF BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This research investigates the impact of preconceived notions on the social relationships of physically challenged learners at Bestlink College of the Philippines. People with physical disabilities often face prejudice and discrimination due to their differences from societal norms, which can affect their social interactions and inclusion. The study aims to examine how these preconceived ideas influence the relationships and social experiences of physically challenged students, ultimately contributing to fostering a more inclusive and supportive educational environment. This study utilized a descriptive research design and employed a face-to-face survey questionnaire, ensuring respect for participants and adherence to ethical research practices. The research used the standardized Stigma or Discrimination Scale, developed by Graham Thornicroft, to comprehensively examine the impact of preconceived notions on the social relationships of 50 physically challenged learners at Bestlink College of the Philippines. The study shows that most respondents are aged between 21 and 25, with female respondents outnumbering males in terms of educational level. Visual impairment is the most common physical disability among the participants. The results highlight that respondents feel the greatest impact from being treated positively, with a mean score of 3.08. This suggests that positive interactions and support from family and others have a significant influence on improving the social experiences of individuals with physical disabilities. Based on the data gathered, physically challenged learners are significantly impacted by positive interactions in their social relationships. To reduce the barriers that individuals with physical disabilities face, efforts should focus on promoting inclusivity and improving access to services. By encouraging understanding and acceptance, we can foster a more inclusive environment. Additionally, providing guidance and support will help individuals with physical disabilities lead more fulfilling lives, ultimately enhancing their overall well-being.
Keywords: physically challenged learners; preconceived notions; social relationships; discrimination; positive interactions; physical disabilities; stigma; inclusion; barriers; support; guidance; accessibility; fulfilling lives; bestlink college of the philipp